Analyzing the stages of consumer purchasing response towards previous user experiences with products using AIDA model: A study conducted on a group of consumers from the city of Bordj Bou Arreridj - Ladour, Soria; Bouabdallah, Hiba (International journal of economic perspectives, 2024)
This research paper aims to acknowledge the extent to which consumers rely on previous user experiences with products in their purchasing decisions by tracking the stages they go through, relying on AIDA model, which consists of four sequential stages: attention, interest, desire, and action. To achieve the research objectives, a questionnaire consisting of 17 statements was designed and distributed to a sample of consumers in the city of Bordj Bou Arreridj. After analyzing the questionnaire with (SPSS, V25), the most important results reached were the general trend of the research sample items with a high degree of agreement towards purchasing products based on users’ previous experiences.